Ultrastructure of Porcine Pericardium and Aortic Valve Tissues, Devitalized with Cryogenic and Irradiation Exposures - Repin, Nikolay V.; Marchenko, Larisa N.; Govorukha, Tatiana P.; Mikhailova, Irina P.; Manchenko, Anna A.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
This paper deals with morphological assessment of cryo- and radiodevitalized tissue biomaterial, i. e. pericardium and aortic valve as well as a cell-free xeno-carcass designing. Structure of the studied tissues after low temperature, ionizing and combined exposures was investigated by optical and electron microscopies. The application of this method to devitalize the pericardium and aortic valve is shown to result in the expressed destructive changes of cell elements, but the spatial location and structural integrity of connective tissue fibrous components are preserved. Probl Cryobiol Cryomed 2015; 25(3):246-254.